Emotional impact associated with the loss or death of a pet - Cartolin, Ximena (2020)
The aim of this study was to determine the perceptions about the emotional impact that the loss or death of the companion animal produces in the lives of its owners. For this, an observational descriptive study based on interviews was designed. One hundred surveys were conducted, and it was found that 87 and 9% of the respondents had dogs and cats, respectively. The average age of acquisition was 0.8 and 0.2, and average holding ownership of 7.6 and 2.6 years, for dogs and cats, respectively. The predominant reasons for tenure were liking towards animals (39%) and the company they gave (35%). Frequent ways of obtaining were gift (52%), purchase (27%) and adoption (19%). Most rated their tenure as very important (62%) and important (34%). The interviewees manifested feeling towards their animal as feelings of love / affection (43%), joy / happiness (27%) and tenderness (17%). The reciprocity of the animal, according to the respondents, was mainly expressed with wagging tail (22%), licking (15%) and following the owner (11%). The main perceived benefit was the company (77%). The majority considered it part or member of the family (55%). Play (96.3%) and walk (93%) were the activities that they carried out daily. The main causes of loss were disease (37%), old age (22%) and disappearance (15%). The initial feeling caused after the loss of the pet was sadness/grief / nostalgy (62%). Among participants, 86% commented that the loss altered their lives a little, 6% a lot and 8% did not affect them. The feeling regarding the lost companion animal at the time of the survey was sadness (31%) and good memory (22%). The holding of a new animal sought to replace the loss produced. The loss of a pet must be properly addressed to contain the emotional impact on owners.